Educação inclusiva de crianças com deficiências na zona rural (vicinal 10) do município Brasil Novo-Pará - GOIS, Luciana Ferreira (2021)
The inclusion of people with disabilities is a topic that has been debated for some time, and even then, society questions about the inclusion of people with disabilities, expressing exclusion behaviors that have rights to education, health, employment, leisure and In this work we will address the theme "Inclusive education of children with disabilities in the rural area (vicinal 10) of the Municipality of Brasil Novo - Pará", because it is understood that this community has many children and adolescents with disabilities, and both are outside of school space, even though some are enrolled, do not attend school and families have not bothered to take them. The work evaluates a bibliographical methodology and a field research in the community of Km 10, including four parents of children with disabilities and four teachers, all participants of the research come from the Vicinal community of km 10, the field research includes questionnaires with questions both for parents as well as teachers. The goal is to describe why children with disabilities are out of school. The research findings conclude why the parents and the school have not worked hard to get children involved in the school context, both are knowledgeable about the rights of the disabled in that community.